(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This study explores the cultural and linguistic significance of proverbs containing the names of medical personnel in English and Uzbek. Through a comparative analysis, it identifies common themes, cultural values, and the role of medical professionals in both societies. The findings reveal how proverbs reflect societal attitudes towards health, medicine, and medical practitioners.